Implementation of Sharia Micro-Financing in Bank Syariah Indonesia Surabaya - Rizki Alamsyah; Ika Yunia Fauzia; Teguh Imami (Universitas KH. Abdul Chalim Mojokerto, 2025)
Sharia microfinancing is considered a strategic instrument in supporting inclusive finance and the growth of MSMEs (Micro, Small, and Medium Enterprises) as the backbone of the national economy. However, this instrument remains limited by financing access, the sharia financial literacy, and technology utilization; thus, a sustainable and effective financing ecosystem model should be developed. This study aims to describe the sharia microfinancing ecosystem model and the distribution practices of microfinancing on MSMEs of Bank Syariah Indonesia (BSI) Surabaya HR Muhammad 1 Branch by utilizing a qualitative approach and case study methods. The result demonstrates that sharia micro financing in BSI involves diverse actors, including the bank, MSME clients, regulatory bodies, and business communities; by implementing sharia principles, for instance, transactions without riba (usury), maisir (speculation), or gharar (uncertainty), as well as using murabaha (cost-plus financing) and musharakah (sharing and partnership financing) agreement. Some products offered are Sharia KUR (People’s Business Credit) and Micro Business BSI - non KUR (non-PBC), with a credit ceiling up to IDR 500 millions. They are also supported by digital innovation, such as the I-Kurma application and the BSI Agent program. The financing scheme implementation positively affects MSMEs' growth, as observed through increasing sales volume and business expansion. However, some challenges remain present, such as a low level of literacy within the society regarding Sharia financing products and administrative problems in the digitalization process. Therefore, this research recommends BSI to advance its sharia financial education program, optimize its digital system, and strengthen risk management to improve the efficiency of sustainable sharia micro financing.